Mandibulada bilateral dentigeröz kist: vaka raporu - Ihsan Levet Aral; Yavuz Tolga Korkmaz (Cumhuriyet University, 2011)
Dentigerous cysts are common developmental cysts of the jaws, most frequently associated with impacted mandibular third molar teeth. Usually they are diagnosed on routine dental radiographs and there is usually no pain or discomfort associated with the cyst unless it becomes secondarily infected. Bilateral dentigerous cyts are rare and typically occurs in association with a developmental syndrome. In addition the occurrence of bilateral dentigerous cysts in the absence of a developmental syndrome is very rare. The aim of this paper was to report on a nonsyndromic, 63 year old man who presented mandibular bilateral dentigerous cyts. ÖZET Dentigeröz kistler çenelerde sık gözlenen odontojenik kistler olmakla beraber, çoğunlukla gömülü mandibular 3. molar dişlerle ilişkilidirler. Genellikle rutin dental radyografilerde tespit edilirler ve sekonder olarak enfekte olmadıkları sürece ağrı veya başka bir rahatsızlık oluşturmazlar. Bilateral dentigeröz kistler nadirdir ve tipik olarak bir gelişimsel sendromla ilişkili olarak ortaya çıkarlar. Buna ek olarak herhangi bir gelişimsel sendrom yokluğunda bilateral dentigeröz kist oluşumu da çok nadir gözlenir. Bu makalenin amacı herhangi bir sendromu olmayan, 63 yaşındaki erkek hastada gözlenen bilateral dentigeröz kist olgusunu sunmaktır. Anahtar kelimeler: Dentigeröz kist, enükleasyon, mandibuler patoloji